Features of strategy development of social responsibility of oil and gas enterprises - Мацьків, Р. Т. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article deals with the processes and peculiarities of development of corporate social responsibility at Ukrainian enterprises. The author has developed an improved mechanism of managing oil and gas enterprises’ responsibility to local communities. The social responsibility strategy is the inalienable element of as company general development strategy, as of enterprise.